The effect of high hydrostatic pressure on the physiological and biochemical properties of pepper (Capsicum annuumL.) seedlings - Islek, Cemil; Altuner, Ergin Murat; Alpas, Hami (Informa UK Limited, 2015)
High hydrostatic pressure is a non-thermal food processing technology, which also has several successful applications in different areas besides food processing. In this study, Capsicum annuum L. (pepper) seeds are subjected to 50, 100, 200 and 300 MPa pressure for 5 min at 25°C and the seedlings of HHP processed seeds are used to compare percentage of seed germination and biochemical properties such as chlorophyll a, b and a/b, proline content, total protein, carotenoid, malondialdehyde, glucose, fructose and phenolic compounds concentrations. As a result of the study, it was observed that there are remarkable changes in terms of biochemical properties especially for seedlings, whose seeds were pressurized at 200 and 300 MPa. More detailed studies are needed to put forward the mechanism behind the changes in biochemical properties.
Keywords: Capsicum annuum; pepper; biochemical properties; high hydrostatic pressure processing; physiological properties; 2. Zero hunger